Sociodemographic, Clinical, and Behavioral Factors Associated with Sexual Transmitted Infection among HIV-1 Positive Migrants in Portugal - the BESTHOPE Study Group (2024)
Funding Information: This study was supported by European Funds through grant \u2018Bio-Molecular and Epidemiological Surveillance of HIV Transmitted Drug Resistance, Hepatitis Co-Infections and Ongoing Transmission Patterns in Europe\u2014BEST HOPE\u2014(project funded through HIVERA: Harmonizing Integrating Vitalizing European Research on HIV/Aids, grant 249697); by FCT for funds to GHTM-UID/Multi/04413/2013 and GHTM-UID/04413/2020; by the MigrantHIV project (financed by FCT: PTDC/DTP-EPI/7066/2014), by Characterization of drug-resistance TB and HIV, and associated socio-behavioral factors among migrants in Lisbon, Portugal project financed by Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia to GHTM-UID/04413/2020 and LA-REAL-LA/P/0117/2020.GHTM-UID/Multi/04413/2013 and by Integriv project (financed by FCT: PTDC/SAU-INF/31990/2017). Publisher Copyright: © 2024 by the authors.